Chemical composition of Apodanthera biflora, a Cucurbit of the dry forest in northwestern Peru - Clark, Daniel (2012)
The dry forest of northwestern Peru is the habitat of numerous native species that have received little attention beyond taxonomic purposes. Here we report the chemical composition of the roots and seeds of a set of accessions of Apondanthera biflora, a wild Cucurbit with potentialities as a food resource. The roots show features that are comparable to those from cassava roots and potato tubers: a high content of carbohydrates on a dry matter basis (77.5 – 84.9%), with starch representing around 20% of the total dry matter. The seeds’ fat content on a dry matter basis (22.22 – 39.37%) falls within the percentages found in oily seeds such as safflower, whereas the protein content (21.37 – 29.06%) is similar to that of flax and sunflower. The fatty acid profile of the seed’s oil shows a predominance of polyunsaturated acids, in particular linoleic acid (43.81%), making it comparable to that of cotton oil. Our results confirm the nutritional value of Apodanthera biflora and set the ground for its use in domestication and food security programs.